Analysis of early patients outcomes after subarahnoid hemorhage depending of it`s complications - Tsoma, Eugenia; Smolanka, Volodymyr; Capec, Szergej (ScienceRise: Medical Science, 2019)
Aim. The purpose of our article was to analyze all cases of non-traumatic SAH that have been treated at our clinic since January 2013 to December 2016 and determine the impact of the complications that can affect on the early patient`s outcome. Materials. Database included 127 patients with subarachnoid hemorrhage that were treated at the Regional Clinical Center for Neurosurgery and Neurology in Uzhgorod during 2013-2016. Extended analysis of the data was performed. The influence of various factors (intracerebral hematoma, symptomatic vasospasm, repeated rupture of aneurysm) on the early patient`s outcome was determined. Result. It was found that more than a half of the patients (70 people) experienced certain types of complications and only 41.7 % of patients had no complications at all. The most common complications were: intracerebral hematoma, intraventricular hemorrhage or their combination, as well as symptomatic vasospasm. According to our data, they were met with the same frequency of ~ 26-28 %. Rarely, occlusive hydrocephalus and re-rupture of the aneurysm occurred (7 % and 13 %). Mortality among patients with complications was 24 % - symptomatic vasospasm, 28 % - occlusive hydrocephalus, 17 % - intraventricular hemorrhage, 28 % - intracerebral hematoma, but in case of re-rupture of the aneurysm - up to 62.5 %. It is one of the most unfavourable factors for early outcome after SAH (p <0.001). Conclusions. Thus, according to our data, the most unfavourable SAH complication for early outcome is symptomatic cerebral vasospasm and repeated rupture of the aneurysm, slightly less - occlusive hydrocephalus and parenchymal hemorrhage. No significant influence of the presence of intraventricular haemorhage on the initial computed tomography after SAH was found